Chronic Heart Failure and Inflammation: What Do We Really Know?. Issue 1 (24th June 2016) - Dick, Sarah A.; Epelman, Slava
Abstract : As a greater proportion of patients survive their initial cardiac insult, medical systems worldwide are being faced with an ever-growing need to understand the mechanisms behind the pathogenesis of chronic heart failure (HF). There is a wealth of information about the role of inflammatory cells and pathways during acute injury and the reparative processes that are subsequently activated. We discuss the different causes that lead to chronic HF development and how the sum of initial inflammatory and reparative responses only sets the trajectory for disease progression. Unfortunately, comparatively little is known about the contribution of the immune system once the trajectory has been set, and chronic HF has been established—which clinically represents the majority of patients. It is known that chronic HF is associated with circulating inflammatory cytokines that can predict clinical outcomes, yet the causative role inflammation plays in disease progression is not well defined, and the majority of clinical trials that target aspects of inflammation in patients with chronic HF have largely been negative. This review will present what is currently known about inflammation in chronic HF in both humans and animal models as a means to highlight the gap in our knowledge base that requires further examination.